Calcipotriol plus betamethasone dipropionate gel compared with calcipotriol scalp solution in the treatment of scalp psoriasis: a randomized, controlled trial investigating efficacy and safety in a Chinese population. (20th June 2015) - Ma, Li; Yang, Qinping; Yang, Haizhen; Wang, Gang; Zheng, Min; Hao, Fei; Gu, Jun; Sun, Qiuning; Cui, Pangen; Ge, Mengliang; Li, Ruoyu; Gao, Tianwen; et al.
Abstract: Background: Calcipotriol/betamethasone dipropionate combination in a non‐alcoholic, lipophilic gel formulation (two‐compound gel) has previously been demonstrated as a safe and effective treatment for scalp psoriasis in Caucasian, Hispanic/Latino, and Black/African American populations. The purpose of this randomized, investigator‐blinded, active‐controlled, 4‐week study was to evaluate the efficacy and safety of the two‐compound gel in Chinese subjects with scalp psoriasis. Method: Subjects were randomized in a 1 : 1 ratio to four weeks of treatment with either the two‐compound gel once daily or calcipotriol scalp solution twice daily. Subjects were evaluated after one, two, and four weeks of treatment. The primary efficacy endpoint was the proportion of subjects who achieved "controlled disease" defined as "clear" or "minimal" disease according to investigator's global assessment of disease severity at week 4. Results: The proportion of subjects who achieved "controlled disease" at week 4 was statistically significantly higher in the two‐compound gel group (87.5%) than in the calcipotriol solution group (50.8%), ( P  < 0.0001). Greater and more rapid improvements with the two‐compound gel were also observed in clinical signs (redness, thickness, and scaliness) and itching. The two‐compound gel was associated with fewer adverse drug reactions than calcipotriol scalp solution (18.6% vs. 33.1%) ( P  = 0.011). Conclusions: The calcipotriol/betamethasone dipropionate gel applied once daily was significantly more effective and better tolerated than calcipotriol scalp solution applied twice daily in the treatment of scalp psoriasis over four weeks in Chinese subjects.